The Effectiveness of Animated Video to Teach First Grade Students of Starlight Tuition in Mastering Number - Dina Kartikawati (STKIP PGRI Trenggalek, 2022)
Teaching English for young learner is not a simple thing. They need different treatment in learning new things especially new language. Some teachers use games, videos, songs, etc. The researcher made an animated movie about “Numbers”. It can be used to teach first grade students to learn Numbers in English from one to ten. The researcher wants to know whether the video made is effective or not to teach first grade students in Starlight Tuition. The result is animated video is effective to teach vocabulary especial “Numbers” to young learner.